2005
DOI: 10.1161/01.cir.0000160867.23556.7d
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein–Coupled Receptor Mas Is a Physiological Antagonist of the Angiotensin II Type 1 Receptor

Abstract: Background-We previously identified the G-protein-coupled receptor Mas, encoded by the Mas proto-oncogene, as an endogenous receptor for the heptapeptide angiotensin-(1-7); however, the receptor is also suggested to be involved in actions of angiotensin II. We therefore tested whether this could be mediated indirectly through an interaction with the angiotensin II type 1 receptor, AT 1 . Methods and Results-In transfected mammalian cells, Mas was not activated by angiotensin II; however, AT 1 receptor-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
312
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(342 citation statements)
references
References 29 publications
16
312
0
2
Order By: Relevance
“…Thus, as demonstrated previously in Mas knockout mice, this receptor seems to be essential for vascular biological actions of Ang- (1-7). 18,25,26 Although we cannot exclude an interaction of Mas with Ang II type 1 or type 2 receptors, 27,28 we have obtained enough evidence in this study to suggest a primary role for Mas, at least, in Ang-(1-7)-induced NO release.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, as demonstrated previously in Mas knockout mice, this receptor seems to be essential for vascular biological actions of Ang- (1-7). 18,25,26 Although we cannot exclude an interaction of Mas with Ang II type 1 or type 2 receptors, 27,28 we have obtained enough evidence in this study to suggest a primary role for Mas, at least, in Ang-(1-7)-induced NO release.…”
Section: Discussionmentioning
confidence: 77%
“…Binding studies showed that Ang-(1-7) binds a receptor, which was completely blocked with the addition of D-Ala 7 -Ang-(1-7) (Tallant et al 1997), suggesting involvment of the mas receptor. Therefore, it is known that Ang-(1-7) binds the mas receptor and is a least partially responsible for the physiological effects reported for Ang-(1-7), but given the current data on interactions of the different angiotensin receptors (Castro et al 2005;Kostenis et al 2005), we do not even come close to understanding the roles of the angiotensin receptor types as they pertain to their physiological actions and/or interactions. The role of this newly reported Ang-(1-7) receptor remains to be elucidated, and its functional significance may bring scientists to a better understanding of how the system functions not only within itself, but also with other endogenous physiological systems.…”
Section: Pharmacodynamicsmentioning
confidence: 81%
“…A particular example is the heptapeptide Ang-(1-7), which is derived from Ang I and Ang II by several metalloproteinases and endopeptidases including ACE2 and neprilysin. Ang-(1-7) has been shown to activate its own seventransmembrane G protein-coupled receptor called Mas (9,10). Mas is expressed on various tissues of the central nervous (CNS) and cardiovascular system (11).…”
mentioning
confidence: 99%